Ameliorative Effects of Silicon against Salt Stress in Gossypium hirsutum L. - Leilei Li; Qian Qi; Hengheng Zhang; Qiang Dong; Asif Iqbal; Huiping Gui; Mirezhatijiang Kayoumu; Meizhen Song; Xiling Zhang; Xiangru Wang (MDPI AG, 2022)
Silicon (Si) could alleviate the adverse effect of salinity in many crops, but the effect in cotton remains unclear. In this study, we evaluated the role of Si in regulating the salt stress tolerance of cotton by analyzing the induced morpho-physiological changes. A hydroponic experiment was conducted by using contrasting salt-tolerant cotton genotypes (sensitive Z0102; tolerant Z9807) and four treatments (CK, control; CKSi, 0.4 mM Si; NaCl, 150 mM NaCl; NaClSi, 150 mM NaCl+0.4 mM Si). The results showed that Si significantly enhanced the net photosynthesis rate and improved the growth of cotton seedling under salt stress in both salt-sensitive and salt-tolerant genotypes. Exogenous Si significantly reduced the accumulation of reactive oxygen species (ROS) and decreased the malondialdehyde (MDA) content in salt-stressed cotton. In addition, the application of Si up-regulated the expression of CAT1, SODCC and POD, and significantly enhanced the antioxidant enzymatic activities, such as catalase (CAT) and peroxidase (POD), of the salt-stressed cotton seedlings. Further, Si addition protected the integrity of the chloroplast ultrastructure, including key enzymes in photosynthesis such as ferredoxin-NADP reeducates (FNR), ATP synthase (Mg2+Ca2+-ATPase) and ribulose-1, 5-bisphosphate carboxylase/oxygenase (RubisCO), and the structure and function of the photosynthetic apparatus PSII from salt stress. Moreover, Si significantly increased the effective stomatal density and stomatal aperture in the salt-stressed cotton seedlings. Taken together, Si could likely ameliorate adverse effects of salt stress on cotton by improving the ROS scavenging ability and photosynthetic capacity.